Growth and performance of fully online and blended K-12 public schools - Charisse Gulosino; Gary Miron (Arizona State University, 2017)
This study provides a census of full-time virtual schools and blended schools from 35 states. Specifically, it utilizes data visualization and exploratory data analysis to examine student demographics and school performance measures of virtual schools and blended schools operating in the 2014-15 school year. The school achievement measures for both virtual and blended schools indicate these schools are performing poorly. Nevertheless, the evidence suggests that their enrollment growth continues. Large virtual schools operated by for-profit education management organizations (EMOs) dominate this sector and are increasing their market share. While more districts are opening their own virtual and blended schools, the schools are typically small, and with limited enrollment. The proportion of Black and Hispanic students in virtual schools is lower than the national average, while students enrolled in blended schools more closely resemble the race and ethnic characteristics of students enrolled in brick-and-mortar public schools nationwide. Virtual and blended schools, while serving students in kindergarten through grade 12, have higher concentrations at the elementary and secondary levels. The empirical work in this area is in its infancy; hence, this study seeks to contribute to both the conceptual and empirical implications of virtual and blended schools by embracing a balance between their public and private benefits.